Reasons for Not Receiving Treatment in People With Posttraumatic Stress Disorder Following War - Janković, Jelena (Array, 2011)
The aim of the study was to explore why people suffering from posttraumatic stress disorder (PTSD) following war do not receive treatment. A total of 212 participants who have PTSD following war in the Balkans and have never received psychiatric treatment were interviewed (86 in Western Europe and 126 in Balkan countries). Answers were subjected to thematic content analysis. Five major and not mutually exclusive themes were identified: "need no help" (57 participants), "personal ways of coping" (72 participants), "negative attitude towards psychiatric treatment" (91 participants), "comparative insignificance" (24 participants), and "external barriers" (65 participants). While most participants, for different reasons, did not want to seek psychiatric treatment, a significant number, particularly in Western European countries, felt prevented from receiving treatment.